Efficacy of magnetic resonance imaging in assessment of myometrial invasion of carcinoma endometrium - James, Sheen Maria; Ambooken, Robert P.; K., Rahul Raj; Krishnan, Vipin; Joseph, Manu (International Journal of Research in Medical Sciences, 2019)
Background: Endometrial carcinoma is the fourth most common cancer in females and the most common malignancy of the female reproductive tract. The prognosis of endometrial carcinoma depends on a number of factors, including stage, depth of myometrial invasion, lympho-vascular invasion, nodal status and histologic grade. Preoperative assessment with MRI is essential for planning surgery and lymph node sampling. The objectives of this study were to determine the myometrial invasion of endometrial carcinoma by MRI and to obtain histopathology in surgically resected specimen, to compare the MRI findings of myometrial invasion in endometrial carcinoma with histopathology in respectable cases. Methods: Authors analyzed 41 cases in whom, histopathological diagnosis of carcinoma endometrium was established by means of pre-treatment biopsy. Consenting patients were taken up for preoperative MRI FIGO staging. MR images were reviewed for parameters like depth of myometrial invasion. Further surgical management followed by histopathological FIGO staging was done. Results: The study showed MRI was highly sensitive and specific tool for identifying depth of myometrial invasion, cervical invasion, serosal invasion, vaginal and parametrial invasion. Conclusions: There was statistically significant difference between histopathological and MRI assessment of local invasion of endometrial carcinoma.